1983
DOI: 10.1111/j.1600-0897.1983.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization in Human Term Placental Bed and Amniochorion of Cells Bearing Trophoblast Antigens Identified by Monoclonal Antibodies*

Abstract: The monoclonal antibodies (mAb) H315, H317, and OKT9 have been used in immunofluorescence to investigate the expression of fetal trophoblast membrane antigens by cells within human term amniochorionic membranes and the marginal area of term placental bed tissue. OKT9 reacted only with trophoblast of placental chorionic villi and did not react with any nonvillous cytotrophoblast population: this mAb is known to identify the cell surface receptor for transferrin. H315 identifies a trophoblast-specific cell-surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The murine mAb 18–6, which recognises an acrosome‐associated antigen 32 was kindly provided by Professor Harry Moore (University of Sheffield, UK). An unrelated mAb prepared in‐house, H317, was also used as a negative control 33 . Texas Red (TR)‐conjugated antimouse IgG was obtained from Molecular Probes (Europe).…”
Section: Methodsmentioning
confidence: 99%
“…The murine mAb 18–6, which recognises an acrosome‐associated antigen 32 was kindly provided by Professor Harry Moore (University of Sheffield, UK). An unrelated mAb prepared in‐house, H317, was also used as a negative control 33 . Texas Red (TR)‐conjugated antimouse IgG was obtained from Molecular Probes (Europe).…”
Section: Methodsmentioning
confidence: 99%
“…The H317 hybridoma had been produced after immunization with isolated plasma membrane preparations from syncytiotrophoblast microvilli of normal human term placentae (Johnson et al, 1981;Johnson & Molloy, 1983). This mAb is specific for the heat-stable, L-phenylalanine-inhibitable, PLAP isoenzyme and is unreactive with other AP isoenzymes from normal human tissues (McLaughlin et al, 1982(McLaughlin et al, , 1984a A sensitive solid-phase EIA using the H317 mAb, described in detail previously (McLaughlin et al, , 1984a, was used to determine active PLAP in sera collected prior to laparotomy and in fresh tumour tissue extracts.…”
Section: Monoclonal Antibodymentioning
confidence: 99%
“…They suggested that these antibodies recognize substances similar to pregnancy-associated proteins which could either be produced by glandular tissue and actively taken up by trophoblast or be produced by trophoblast and absorbed by glandular epithelium. The former possibility was dismissed by the authors as unlikely on the assumption that no glands were present in the placental bed at term, yet trophoblast from term placenta continued to show reactivity to the monoclonal antibodies (Johnson et al, 1981;Johnson and Molloy, 1983). The current study's identification of glands active in glycoprotein synthesis at term again raises the possibility that they could have a role in secreting the antigen recognized by the two monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 65%